The ability to rational relaxation of the muscles in children who are engaged in football taking into account their nervous system (Bangladesh Journal of Medical Science, 2021)
Introduction: If the football lessons with children take into account their strength of thenervous system in the process of excitation, the effectiveness of such activities will be higher.Objective: Study of the effect of the nervous system of players on the ability to rationally relax their muscles.Method: 44 athlete’s aged 13-14 years took part in the pedagogical experiment.22 young footballers were engaged in the experimental methodic, which is based on the useof different components of the load, for players with a strong nervous system (11 people) theload was intense, and for players with a weak nervous system (11 people) - volume. Other 22athletes were in the control group.Results: After 7 months of research, we saw a significantimprovement in the ability to relax the muscles in children aged 13-14 years, who trainedaccording to our methodic. Children who have a strong nervous system, improved performancein the test “juggling the ball” from 4.1±0.8 times to 6.5±1.1 times (P